Targeting and Scaling Out - CGIAR Challenge Program on Water and Food (CGIAR Challenge Program on Water and Food, 2013)
The project will develop an evidence and know- ledge-based tool to assess and map the likelihood that a given intervention will be successful in given locations, at the basin scale. The project seeks to answer the question of what works where and why